2013
DOI: 10.1186/1471-2407-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with peritoneal metastasis in non-serosa-invasive gastric cancer: a retrospective study of a prospectively-collected database

Abstract: BackgroundPeritoneal dissemination is the most common type of recurrence in advanced gastric cancer. The main mechanism is thought to be via the exfoliation of free cancer cells (FCCs) from tumor in the gastric serosa. The frequency of recurrence thus increases once the tumor cells penetrate the serosa. However, this type of recurrence also occurs in patients without serosal invasion, though the mechanisms responsible for have not been fully established. We therefore investigated the factors associated with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 17 publications
(19 reference statements)
1
23
1
Order By: Relevance
“…Similarly, Song et al found that T3 stage patients with INFc pattern had more frequent peritoneal recurrence than those with INFa/b pattern 14. In the previous research, we also had reported that INFc pattern was independently associated with peritoneal metastasis in patients with GC without serosal invasion 17. Although the inconsistent results still exist in several studies, we believed that the prognostic significance of INF pattern in patients with advanced GC should not be ignored.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, Song et al found that T3 stage patients with INFc pattern had more frequent peritoneal recurrence than those with INFa/b pattern 14. In the previous research, we also had reported that INFc pattern was independently associated with peritoneal metastasis in patients with GC without serosal invasion 17. Although the inconsistent results still exist in several studies, we believed that the prognostic significance of INF pattern in patients with advanced GC should not be ignored.…”
Section: Discussionmentioning
confidence: 66%
“…The detailed pathological features of three INF patterns were shown as we reported previously (figure 1). 17 INFa was described as the tumour lesion that showed a expanding growth and a distinct border with the surrounding tissue. INFc was described as the tumour lesion that exhibited a infiltrating growth and a indistinct border with the surrounding tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 40% of gastric cancer cases occur in China, and many are diagnosed at an advanced stage with a tendency toward metastasis and recurrence [4]. Peritoneal carcinoma occurs in both the advanced and early stages of gastric cancer and is the most common type of metastasis and recurrence [57]. The median survival of patients with peritoneal metastasis is less than 6 months due to the development of resistance to therapy [811].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, enrolled patients had a median clinical follow-up of 51.7 mo, which was considerably longer than previous studies (13,15,20). Our study showed that 18 F-FDG uptake of gastric cancer remained an independent prognostic factor for recurrence-free survival and overall survival in AGC patients, along with pT stage, lymph node metastasis, and lymphovascular invasion, which were already known to be significant prognostic factors (5,(22)(23)(24). Different from these prognostic factors, 18 F-FDG PET is advantageous in providing prognostic information even before surgery.…”
Section: Discussionmentioning
confidence: 47%